Visualizing educational opportunities through TIC - Durán-López, Marlene (2017)
Good teaching practices help schools to conceive technology in a responsible, ethical and equitable way. Thinking of the generation of learning in a holistic way leads to the visualization of technology, not as the end, but as the means to achieve objectives. Understanding the new technological trends from a critical and relevant perspective opens a panorama that translates into opportunities for integral growth of all the people involved in the process of teaching and learning. We might ask the question proposed by Lévy (2007):How can we keep our teaching practices in a way that meets the requirements of these new processes of transaction knowledge? It is not a question of using technology at any cost, but of accompanying, consciously and deliberately, a civilization change that will deeply challenge, again, institutional forms, mentalities, and the culture of traditional education systems and, above all, the roles of the teacher and the student.These new roles are presented in the context of new technology scenarios and should be designed within a strategy providing equal opportunities that will empower actors to maintain the culture and identity in front of the globalization and the barriers an information society presents to a knowledge society.